Efficacy of N-acetylcysteine in Acute Paraquat Poisoning: An Open-label, Parallel-group, Randomized Controlled Trial - Cheekatla Venkata Santosh; Mandip Singh Bhatia; Atul Saroch; Navneet Sharma; Neeraj Singla; Saurabh Chandrabhan Sharda (APIK Journal of Internal Medicine, 2026)
Abstract Background: Paraquat poisoning is associated with high mortality due to oxidative stress-induced multiorgan failure. No specific antidote is available. N-acetylcysteine (NAC) has shown potential benefit in preclinical studies, but robust evidence of its clinical efficacy is lacking. Objectives: This study was designed to evaluate the effects of intravenous NAC on organ dysfunction and mortality among patients with acute paraquat poisoning. Methods: We conducted an open-label, parallel-group, randomised controlled trial at a tertiary care center in northern India. Adults (≥18 years) presenting within 5 days of oral paraquat ingestion were randomized 1:1 to receive standard supportive care plus intravenous NAC (a total 21-h regimen) or standard care alone. The primary outcome was the incidence and severity of acute respiratory distress syndrome (ARDS). Secondary outcomes included the incidence of acute kidney injury (AKI) and acute liver injury (ALI), the need for renal replacement therapy (RRT), and 14-day all-cause mortality. Results: Fifty-two patients (26 per group) were included in the per-protocol analysis. Baseline demographics and clinical severity scores (median APACHE II: 12 vs. 11) were comparable between the groups. ARDS occurred in 100% of the NAC group and 96.2% of the control group ( P = 0.313), with no significant difference in severity. The incidence of AKI (96.2% vs. 92.3%; P = 0.552), RRT requirement (76.9% vs. 69.2%; P = 0.532), and ALI (96.2% vs. 92.3%; P = 0.552) was similar. Mortality at 14 days was high in both groups (96.2% vs. 88.5%; P = 0.298). Kaplan–Meier analysis showed no significant difference in survival (log-rank P = 0.69). Conclusion: In this trial of patients with severe paraquat poisoning, adding intravenous NAC to standard care did not reduce the incidence of organ dysfunction or improve 14-day survival.